Risk Minimization Strategy for Apple Dodol Supply Chain with Analytical Hierarchy Process Approach (Case Study in SMESBROSEM, Batu City, East Java) - Mustaniroh, Siti Asmaul; Wulandari, Mey; Santoso, Imam (International Journal of Social and Local Economic Governance, 2017)
One of the producers of apple dodol in Batu is SMESBrosem, which applies a supply chain system consisting of the supplier, producer, and retailer. This application carries potential risks, such as apple supply delay, production delay, and competitors. Therefore, there is a need for alternative strategies in order to reduce these risks. This study aims to organize a strategy that can be applied in SMESBrosem using Analytical Hierarchy Approach (AHP). The proposed strategies that potentially reduce the risks include making a production plan, conducting a workshop for employees, improving information access and collaboration.Keywords: Apple dodol, Strategy, Supply Chain